Ontology-based process integration incorporating reference associations between medical standards from the perspective of medical software developers - Kim, Dong Yeop; Park, Ye Seul; Lee, Byungjeong; Lee, Jung Won (Journal of Ambient Intelligence and Humanized Computing, 2019)
International standards for medical software require systematic development, with the core standards being IEC 60601-1, IEC 62034, and ISO 14971. Three core standards represent five development activities by referring activities undertaken as per other standards. As a result, developers have difficulty identifying the reference relationships. There are studies supporting the reference associations, but they do not provide the associations at each stage of the development. So, we propose an integrated process in which core standards are re-configured from the developer’s point of view and describe as an ontology. By analyzing associations oriented development process, the integrated process is defined corresponding to requirements at each stage of the development procedure. Also, we define the cost required to comply with the standards. By randomly generated scenarios, a cost reduction of 47% can be achieved by suggested process. As a result, the integrated process enables the systematic and effective development of medical software.
Keywords: Development activity; Development process; International standards; Medical software; Ontology-based; Process integration; Reference relationships; Medical software development; Medical standard; Ontology; Process integration